2018
DOI: 10.9755/ejfa.2017.v29.i12.1569
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varied plant density and nitrogen fertilization on quantity and quality yield of Camelina sativa L.

Abstract: False flax (Camelina sativa L.), is an oil plant, of the Brassicaceae (Cruciferae) family. It is a rediscovered crop with multiple uses, it is a frost proof, low-soil and climatic conditions plant. In Poland the variety is not very widespread, despite of its health benefits. The particular value of camelina oil is given by its content in polyunsaturated fatty acid (50-60%), by its content in omega 3 (35-40%) and by its content in omega 6 (15-20%). The seeds are used for the extraction of oil (used in medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…High air temperatures during flowering and seed filling are generally associated with low oil contents but high protein contents within C. sativa seed [ 62 ]. Furthermore, increased N application rates can increase protein contents, with an associated decrease in oil contents [ 73 , 87 , 93 , 94 ]. Such increased nitrogen applications are known to increase protein at the expense of fatty acid synthesis due to the competition for carbon skeleton during carbohydrate metabolism [ 95 ].…”
Section: C Sativa Yield Potential Under Hot and Dry Conditionsmentioning
confidence: 99%
“…High air temperatures during flowering and seed filling are generally associated with low oil contents but high protein contents within C. sativa seed [ 62 ]. Furthermore, increased N application rates can increase protein contents, with an associated decrease in oil contents [ 73 , 87 , 93 , 94 ]. Such increased nitrogen applications are known to increase protein at the expense of fatty acid synthesis due to the competition for carbon skeleton during carbohydrate metabolism [ 95 ].…”
Section: C Sativa Yield Potential Under Hot and Dry Conditionsmentioning
confidence: 99%
“…[26] Previous studies have indicated that the use of optimal planting density can increase the secondary metabolite content of numerous medicinal plants, such as Rheum tanguticum Maxim. ex Balf, [27] Camelina sativa L., [28] yellow gentian [29] and Moringa oleifera. [30] Furthermore, an increase in planting density within a certain range leads to an increase in biomass yield.…”
Section: Introductionmentioning
confidence: 99%
“…1e). The final number of silicles per plant can range from approximately 60 to 115, and it is positively and negatively correlated with increased N fertilization and increased sowing density, respectively (Czarnik et al 2017(Czarnik et al , 2018. At the end of their expansion, silicles are 4-5 mm wide and 6-8 mm long (Martinelli and Galasso 2011).…”
Section: Morphological Description and Main Agronomic Traitsmentioning
confidence: 99%
“…Each silique can contain 10-20 small seeds (Czarnik et al 2017;Jankowski et al 2019;Martinelli and Galasso 2011). In fact, 1000-seed weight varies from 0.7 to 1.8 g (Angelini et al 1997;Czarnik et al 2017Czarnik et al , 2018Jankowski et al 2019;Righini et al 2019;Vollmann et al 2007;Załuski et al 2020;Zanetti et al 2017;Zubr 1997). Older studies report a negative correlation between seed weight and both seed and oil yield.…”
Section: Morphological Description and Main Agronomic Traitsmentioning
confidence: 99%
See 1 more Smart Citation